ECTOPARASITE INFESTATION ON Rattus tiomanicus AS A DISEASE VECTOR AT MOUNT SAGO, WEST SUMATRA - Rachmad Hidayat; Mairawita Mairawita (Program Studi Pendidikan Biologi, 2021)
Malayan wood-rat Rattus tiomanicus (Rodentia, Muridae) is known for common pest in various landscape in Southeast Asia. This rat is not only destructive to the crop plants and other agricultural products, they can become vector for parasites and diseases-borne parasites which are dangerous to human being. This researchaimed to identify and do the inventory on ectoparasites on R. tiomanicus at Mount Sago. The fieldwork had been performed from September to October 2020 using purpovise sampling at three elevations. The trapping yielded 7 individuals of R. tiomanicus. There were 8 ectoparasite spesies with total 360 individuals extracted from trapped rats. Four rats were observed to be infested by Echinolaelaps echidninus was counted as the most numerous ectoparasite with 111 individuals extracted and Xenopsylla cheoips,with 3 only individuals, became the rarest ectoparasite in this study. The diversity index was 1.72 which indicates that the diversity of ectoparasites across their hosts was also moderate. Recall that the number of trapped Rattus tiomanicuswas only few, we presume that the diversity of ectoparasite in Sago Mountain area could be more prominent than what we found.